2023
DOI: 10.1126/sciimmunol.abm6360
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetically controlled tumor antigens derived from splice junctions between exons and transposable elements

Abstract: Oncogenesis often implicates epigenetic alterations, including derepression of transposable elements (TEs) and defects in alternative splicing. Here, we explore the possibility that noncanonical splice junctions between exons and TEs represent a source of tumor-specific antigens. We show that mouse normal tissues and tumor cell lines express wide but distinct ranges of mRNA junctions between exons and TEs, some of which are tumor specific. Immunopeptidome analyses in tumor cell lines identified peptides derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…SETDB-1 –low samples differentially expressed more JETs than SETDB-1 –high samples (fig. S1D), consistent with our results in mouse tumors ( 28 ). These results suggest that TE derepression in tumors can influence JET expression.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…SETDB-1 –low samples differentially expressed more JETs than SETDB-1 –high samples (fig. S1D), consistent with our results in mouse tumors ( 28 ). These results suggest that TE derepression in tumors can influence JET expression.…”
Section: Resultssupporting
confidence: 92%
“…We detected JET-specific T cell responses in tumors and lymph nodes from patients with NSCLC at steady state and after in vitro culture. These findings are consistent with our companion paper showing that murine JETs are immunogenic and protective in vivo ( 28 ). A second technique for the detection of JET-specific T cells in tumors/lymph nodes (such as enzyme-linked immunospot), however, would strengthen the evidence for anti-JET T cell responses in patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported that there are conserved tumor exon junctions between MC38 colon cancer cells B16-F10 melanoma cells that can be presented on MHCI. 29 Additionally, mice exposed prophylactically to conserved tumor exon junctions showed protective effects against B16-F10 growth through induction of anti-tumor immune responses. 29 We speculate that conserved tumor neoantigens between MC38 TEVs and B16-F10 melanoma may undergo immunoediting, thus allowing for immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…29 Additionally, mice exposed prophylactically to conserved tumor exon junctions showed protective effects against B16-F10 growth through induction of anti-tumor immune responses. 29 We speculate that conserved tumor neoantigens between MC38 TEVs and B16-F10 melanoma may undergo immunoediting, thus allowing for immune escape. 30,31 Conversely, the tumor neoantigens conserved between MC38 TEVs and B16-F10 may only stimulate a weak immune response.…”
Section: Discussionmentioning
confidence: 99%